(untitled) (International journal of artificial intelligence, 2025)
the article discusses important aspects of rehabilitation of patients with duodenal ulcer from the point of view of medical and socio-economic efficiency. An analysis of the impact of complex treatment and preventive measures on clinical outcomes and quality of life of patients was performed. Particular attention is paid to the need for an interdisciplinary approach, covering gastroenterological, psychological and social support. It is concluded that the integration of medical and socio-economic criteria in assessing the effectiveness of rehabilitation programs is of great importance, which contributes to a more complete restoration of working capacity and an improved prognosis of the disease.